Adulterantes em café (Coffea arabica L.) torrado e moído e suas implicações na qualidade físico-química e sensorial da bebida - Silva, Vanderley Almeida (2013)
The detection of impurities and mixtures in roast and ground coffee is a constant concern regarding to the guarantee of the product quality. It is essential to inform the consumer, consistently, ensuring a pure product with no defects or variations of fraud. Adulteration is the act of mixing intentionally or not, foreign materials to the product, usually low cost, which affects their quality and cause damage to the consumer, especially to the health and economic. This study employed the spectroscopy in the middle infrared region, sensory analysis and some physical-chemical analyzes associated with principal component analysis (PCA) to identify adulteration in roasted and ground coffee by adding different percentages of husk, saccharine straw and corn in coffee rio drink. This study aimed to investigate efficient and cost-effective identification of adulterated samples alternatives and evaluate the effects caused by the adulteration. Coffee and adulterants were roasted separately at the point of medium dark roast coffee and then milled added different proportions (0, 10, 20, 30, 40 and 50%) of saccharine straw, husk or corn to coffee. The samples were analyzed by means of physico- chemical properties (moisture, ash, crude fiber, ether extract, aqueous extract, crude protein, total sugars, reducing and non-reducing), mid-infrared spectroscopy and sensory analysis (acceptance testing) with in order to discriminate the samples of adulterated pure coffee. The physico-chemical attributes that contributed most to the discrimination of pure coffee was the aqueous extract, which is the parameter that showed the highest correlation with the addition of adulterants analyzed. It was possible to discriminate samples of pure coffee adulterated samples with husk, saccharine straw and corn using mid-infrared spectroscopy and PCA. The results of sensory analysis showed that the inclusion of fraudulent materials modified the natural characteristics of the coffee. In sensory analysis, the sample of pure coffee received the highest score for the attribute overall appearance, but the samples with 20% adulterant generally had equal or superior reviews the pure samples, especially samples containing saccharine straw and corn. However, those with higher levels of corn, husk and saccharine straw (40 % and 50 %), had lowest scores for the attributes color, aroma and taste.